Projection of Streamflow Changes Under CMIP6 Scenarios in the Urumqi River Head Watershed, Tianshan Mountain, China - Yang, Min; Li, Zhongqin; Anjum, Muhammad Naveed; Kayastha, Rakesh; Kayastha, Rijan Bhakta; Rai, Mukesh; Zhang, Xin; Xu, Chunhai (Frontiers in Earth Science, 2022)
Analyzing climate change impacts on hydrology and future water supply projections is essential for effective water resource management and planning in the large river basins of Asia. In these regions, streamflow and glacier melt remain subject to significant uncertainties due to the lack of confidence in climate change projections and modeling methods. In this study, a glacier dynamics model (the Open Global Glacier Model was coupled with a glacio-hydrological model [the Glacio-hydrological Degree-day Model (GDM)] to predict possible hydrological changes in the head watershed of the Urumqi River under three shared socioeconomic pathways SSP2-4.5, SSP3-7.0, and SSP5-8.5. The GDM was calibrated and validated against in situ observed discharge data for the 2007–2011 and 2012–2018 periods. The resulting Nash–Sutcliffe efficiency (NSE) values were 0.82 and 0.81, respectively. The GDM was driven with an ensemble of five downscaled CMIP6 datasets to examine the potential impacts of climate change on hydrologic processes in the basin. Four runoff components were simulated with the GDM: base flow, rainfall, ice melt, and snow melt. It was determined that rainfall constituted the predominant source of runoff, followed by baseflow and ice melt. During the calibration and validation periods, snow and ice melt contributed 25.14 and 25.62%, respectively, to the total runoff. Under all SSP scenarios, the projected runoff decline indicated that the peak runoff time had passed. It was revealed that a 2°C increase in the monthly average temperature could result in a 37.7% increase in the total discharge of the basin. Moreover, the GDM was more responsive to changes in air temperature than to changes in glacier extent.